Fermentation of Mannitol Extracts From Brown Macro Algae by Thermophilic Clostridia - Chades, Theo; Scully, Sean M.; Ingvadottir, Eva M.; Orlygsson, Johann (Frontiers in Microbiology, 2018)
Mannitol-containing macro algae biomass, such as Ascophyllum nodosum and Laminaria digitata, are a potential feedstock for the production of biofuels such as bioethanol. The purpose of this work was to evaluate the ability of thermophilic anaerobes within Class Clostridia to ferment mannitol and mannitol-containing algal extracts. Screening of the type strains of six genera, Caldanaerobius, Caldanaerobacter, Caldicellulosiruptor, Thermoanaerobacter, Thermobrachium, and Thermoanaerobacterium) was conducted on 20 mM mannitol and revealed that 11 of 41 strains could utilize mannitol with ethanol being the dominant end-product. Mannitol utilization seems to be most common within the genus of Thermoanaerobacter (7 of 16 strains) with yields up to 91.5% of the theoretical yield in the case of Thermoanaerobacter pseudoethanolicus. Six selected mannitol-degrading strains (all Thermoanaerobacter species) were grown on mannitol extracts prepared from Ascophyllum nodosum and Laminaria digitata. Five of the strains produced similar amounts of ethanol as compared with ethanol yields from mannitol only. Finally, Thermoanaerobacter pseudoethanolicus was kinetically monitored using mannitol and mannitol extracts made from two macro algae species, Ascophyllum nodosum and Laminaria digitata for end-product formation.